Evaluation of the effect of aromatase inhibitor in reducing the size of endometrioma - Ansary, Selina Afroz; Ishrat, Shakeela; Banu, Jesmine; Fatima, Parveen; Nasreen, Faria; Jahan, Israt; Afrin, Shajia; Nasreen, Khaleda; Mohsin, Mohammad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Endometriosis is a chronic and progressive estrogen-dependent disorder that can result in substantial morbidity, including pelvic pain, multiple operations, and infertility. Endometriosis can be ovarian, peritoneal or deep infiltrative. Blocking estrogen production by inhibiting aromatization, aromatase inhibitor (letrozole) has been shown to reduce the size of endometrioma and endometriosis associated pain. Aim of the study was to evaluate the effect of aromatase inhibitor in reducing the size of endometrioma. Methods: A prospective non comparative observational study was conducted in the Department of Reproductive Endocrinology and Infertility of BSMMU on 30 women with ovarian endometrioma during the period of April 2019 to March 2020. Women were treated with aromatase inhibitor (letrozole) 2.5 mg, norethisterone 5 mg, calcium 1200 mg, and vitamin D 800 IU daily for 6 months. Transvaginal ultrasound was performed at baseline, 3 months and 6 months after treatment to assess the mean diameter and volume of endometriomas. Statistical analyses were carried out by using the Statistical Package for Social Sciences version 23.0. Results: More than 50% reduction in volume occurred in 90% of endometrioma. In one (3.3%) case endometrioma disappeared completely after 6 months. There was statistically significant reduction of size of endometrioma (estimated by mean diameter and volume) and pain. Volume decrease was linearly related to baseline endometrioma volume and inversely related to baseline body mass index (BMI). The side effects were mild and well tolerated by the patients. Conclusions: Treatment of ovarian endometrioma with aromatase inhibitor combined with progestin add-back for 6 months cause substantial reduction in size of endometrioma and associated pain.